PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KAMPUS DAN KOMUNIKASI INTERAKTIF TERHADAP KEDISIPLINAN TARUNA DI POLTEKTRANS SDP PALEMBANG - Fahriza, Deni; Tri Suyantiningsih; Sari Sakarina (IWJ : Inland Waterways Journal, 2024)
The purpose this research is to analyze the influence of leadership style, campus environment, and interactive communication on the discipline of cadets at Politeknik Transportasi SDP Palembang. Discipline is a crucial aspect of cadet education, influencing their success in completing the educational program and preparing them to face challenges in the workforce. However, several factors can affect the level of cadet discipline, including leadership style, campus environment conditions, and the quality of interactive communication between cadets and instructors, as well as among the cadets themselves. This research employs a quantitative approach using a survey method involving 174 cadets as respondents. Data were collected through a questionnaire designed based on a Likert scale and analyzed using multiple linear regression to determine the influence of each independent variable on the dependent variable. The results of the study show that leadership style has a significant impact on cadet discipline, where a democratic leadership style tends to enhance discipline. The campus environment is also found to have a significant influence, where a conducive and supportive environment can improve cadet discipline. Additionally, effective interactive communication between cadets and instructors and among the cadets themselves also plays an important role in promoting discipline.